EXERCÍCIO FÍSICO COMO TRATAMENTO NÃO FARMACOLÓGICO DAS DOENÇAS CARDIOVASCULARES: QUAL A INTENSIDADE IDEAL? - Pablo Antônio Bertasso de Araújo; Samantha Nahas Guimarães; Fernanda Christina de Souza Guidarini (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
There is an agreement that exercise has beneficial effects in patients with cardiovascular diseases. However, controversy exists about the intensity of exercise which produces maximum adjustments. The objective was to examine the best intensity for physical exercise in patients with cardiovascular diseases. The literature review was conducted in all the guidelines and consensus of the Brazilian Society of Cardiology from 1994-2010, related to cardiac rehabilitation and disease: Hypertension, Dyslipidemia and Atherosclerosis, Myocardial Infarction, Chronic Heart Failure. Review was made of articles related to the intensity of exercise for patients with cardiovascular diseases. The results showed that aerobic exercise is highly recommended. The prescribed duration varies from 30-60 minutes. The frequency of 3-5 times/week. The guidelines propose intensities 60-80% of maximum oxygen consumption. Moreover, many studies have shown better results in vascular, cardiac and metabolic with the training of high intensity compared to moderate and low intensity. We conclude that the Brazilian guidelines are conservative and the intensity of exercise. We suggest using moderate and high intensity in rehabilitation programs.